PENGARUH PENDIDIKAN CERAMAH DAN MEDIA VIDEO TERHADAP TINGKAT PENGETAHUAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI PADA SISWI SEKOLAH MENENGAH ATAS - Elida Sinuraya; Rosseti Sipayung; Sri Handayani (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Breast self-examination is an easy way for early detection of breast cancer for all women after they are menstruation. This examination will increase awareness of the importance of being aware of abnormal lumps in the breast. The aims of this study is to determine the effect of education about breast self- examination with video media on the level of knowledge on high school students. This research method was used quasy experimental research design with pre-test and post-test with control group. The population were 15 student in YPI high school Amir Hamzah and 15 student in Kartika I-1 high schools. Random Sampling sampling technique. Researchers used paired t-test and independent t-test test with a <0.05 and 95% CI. The result: the statistical test before and after the intervention: giving explanation with media video are p value =0.09 (<0.05) and in the control group without giving media video with p value 0.07 (<0.05).